The Role of Green Technology in mediating the impact of GCG and Biodiversity Accounting on Energy and Mining Sector Performance - Nisja Putra Zai, Simon; Santosa, Slamet (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) and Biodiversity Accounting on the performance of companies in the energy and mining sectors. This study examines the adoption of green accounting as a mediator between GCG, biodiversity accounting, and company performance. The results showed that GCG and Biodiversity accounting, supported by the adoption of Green accounting, improved company performance. This study uses SEM-PLS to develop specific indicators for latent variables, based on 250 financial statements and sustainability performance. These findings have important implications for companies, governments, and stakeholders in supporting sustainability through the application of GCG principles and green technology. Further Research could extend this review to other sectors and explore the long-term impact of adopting environmentally friendly technologies on company performance.